Determinan Kecurangan Akuntansi Dalam Pengelolaan Dana Desa - Abdul Handi; Ikhsan Budi Raharjo; Wahidahwati . (Jurnal Studi Manajemen dan Bisnis, 2021)
This study aims to Examine and analyze the factors that influence village officials’ tendency to commit fraud in village funds managenment. This study used the village apparatus in Lamongan Regency as respondents. It analyzed one hundred twelve questionnaires for hypothesis testing. In this study, the independent variables were the effectiveness of internal control, information asymmetry, organizational commitment, the suitability of compensation, and individual morality, and fraud as the dependent variable. This study applied multiple linear regression analysistools for hypothesis testing. The results indicated that the information asymmetry had a significant positive effect and negativly impacted accounting fraud in village funds management. Furthermore, The organizational commitment, the suitabiity of compensation, and internal control had no effect on accounting fraud in village funds management.